Thermal response of heterolithic deposits in flooded coal mines: implication for heat storage potential - Mylene Receveur; Andres Gonzalez Quiros; Alison Monaghan; Vanessa Starcher; Kyle Walker-Verkuil; David Boon; Jeroen van-Hunen (Geothermics, 2026)

De-risking green energy from mine waters by developing a robust hydrogeological conceptual model of the UK Geoenergy Observatory in Glasgow - Andres Gonzalez Quiros; Donald John MacAllister; Alan MacDonald; Barbara Palumbo-Roe; Jenny Bearcock; Brighid Ó Dochartaigh; Eileen Callaghan; Tim Kearsey; Kyle Walker-Verkuil; Alison Monaghan (Hydrogeology Journal, 2024)
Mine-water geothermal resources have potential to provide low-carbon heating and cooling in many areas; however, this potential has not been fully realised due to technical, economic and policy challenges. The UK Geoenergy Observatory (UKGEOS) in Glasgow was developed to provide an at-scale research facility designed to help de-risk mine-water geothermal usage. The limited knowledge of the hydrogeological systems altered by former mining activities is a key determinant of the long-term sustainability of water and heat abstraction/reinjection. This work presents a hydrogeological conceptual model developed using groundwater monitoring data obtained during the construction of the Observatory between 2020 and 2022, results from initial pumping tests performed in 2020, and results of hydrochemistry analysis from 25 sampling rounds collected between 2019 and 2022. The analysis of the data provides evidence of the dominant role of mine workings in controlling groundwater flow, with high intra-mine connectivity; increased fracturing in sandstones above mine workings; and limited inter-mine connectivity. Groundwater recharge is meteoric, mean residence times are >50 years, and there is a general upwards circulation from the deeper mine levels to the superficial deposits and the River Clyde. Faults play a significant role in limiting the extent of the highly transmissive mine workings, but there remains uncertainty surrounding the role of the faults in connecting different mine workings and their hydraulic behaviour in nonmined units. The conceptual model, that will be refined as new data become available, will be used to help guide monitoring and sampling programs and plan research activities in the Observatory.